(untitled) (Polish Yearbook of International Law, 2021)
On 1 March 2020, Professor Andrzej Wasilkowski died. In his research, Professor Wasilkowski undertook issues which were co creating the mainstreams of legal debates all over the world. He was an author of valuable publications on the relationship between international law and Polish domestic law. Professor Wasilkowski was also a director of the Institute of Law Studies of the Polish Academy of Sciences and the head of the Legal Advisory Committee of the Minister of Foreign Affairs.